2021
DOI: 10.3390/su132111975
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Corporate Social Responsibility Perceptions in Brand Equity, Brand Credibility, Brand Reputation, and Purchase Intentions

Abstract: Corporate social responsibility (CSR) is becoming one of the most critical challenges that firms must address to survive in the competitive market. This study investigates the impact of customers’ CSR perceptions on their purchase intentions as mediated by brand equity, brand credibility, and brand reputation in order to identify the benefits of CSR integration for business development. The study employs a quantitative approach to collect data from customers who purchase cosmetics through an online survey. PLS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 93 publications
4
36
1
1
Order By: Relevance
“…Similarly, companies engaging in authentic CSR activities may favorably influence consumers’ perceptions, and such actions may enhance the authenticity of their brands (Kim and Lee, 2020). Prior research has demonstrated that a company’s CSR actions (relating to society, environment and stakeholders) are important determinants of a brand’s credibility that assist in enhancing the credibility of a brand (Abu Zayyad et al , 2021; Hur et al , 2014; Wang et al , 2021). Since brand credibility is a component of brand authenticity (Morhart et al , 2015), this study assumes that authentic CSR activities may assist consumers in improving their perceptions of a brand’s authenticity.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Similarly, companies engaging in authentic CSR activities may favorably influence consumers’ perceptions, and such actions may enhance the authenticity of their brands (Kim and Lee, 2020). Prior research has demonstrated that a company’s CSR actions (relating to society, environment and stakeholders) are important determinants of a brand’s credibility that assist in enhancing the credibility of a brand (Abu Zayyad et al , 2021; Hur et al , 2014; Wang et al , 2021). Since brand credibility is a component of brand authenticity (Morhart et al , 2015), this study assumes that authentic CSR activities may assist consumers in improving their perceptions of a brand’s authenticity.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Brand awareness enables buyers to differentiate a brand from others and put it in their consideration set, resulting in positive attitudes and purchase habits (Wang et al, 2021). Brand awareness is influential in customer decisions due to three reasons.…”
Section: Brand Awarenessmentioning
confidence: 99%
“…It is saved in customers' memories and is easily accessible throughout the purchasing process. In addition, brand associations are linked to the target market and induce consumers to make purchases (Wang et al, 2021). The linkage between association and brand will be established more easily if the brand is firmly ingrained in the customers' minds (Esch et al, 2006) and helps customers differentiate between brands and make decisions based on their perceptions of brand association (Liu et al, 2017).…”
Section: Brand Associationmentioning
confidence: 99%
“…Estudios expresan [9], [6], que las instituciones han demostrado gran relevancia en la exploración de nuevas variables de comunicación digital, para la divulgación de su imagen institucional, con la intención de incrementar su visibilidad en los rankings universitarios, e indican que las universidades en Ecuador presentan notables problemas al utilizar e-branding académico como estrategia de divulgación. La responsabilidad social institucional debe proyectar el valor, credibilidad y reputación de la marca ante el público para generar en ellos la intención de compra [10].…”
Section: A Logotipos Como Representación De Maracasunclassified